Homebound versus Bedridden Status among Those with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Conroy, Karl (Healthcare (Basel), 2021)
Persons living with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) vary widely in terms of the severity of their illness. It is estimated that of those living with ME/CFS in the United States, about 385,000 are homebound. There is a need to know more about different degrees of being homebound within this severely affected group. The current study examined an international sample of 2138 study participants with ME/CFS, of whom 549 were severely affected (operationalized as ‘Homebound’). A subsample of 89 very severely affected participants (operationalized as ‘Homebound-bedridden’) was also examined. The findings showed a significant association between severely and very severely affected participants within the post-exertional malaise (PEM) symptom domain. The implications of these findings are discussed.